2022
DOI: 10.1055/s-0042-1748975
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Deaths from COVID-19 in Brazil: Increase during the Second Wave of the Pandemic

Abstract: Objective To compare death rates by COVID-19 between pregnant or postpartum and nonpregnant women during the first and second waves of the Brazilian pandemic. Methods In the present population-based evaluation data from the Sistema de Informação da Vigilância Epidemiológica da Gripe (SIVEP-Gripe, in the Portuguese acronym), we included women with c (ARDS) by COVID-19: 47,768 in 2020 (4,853 obstetric versus 42,915 nonobstetric) and 66,689 in 2021 (5,208 obstetric versus 61,481 nonobstetric) and estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
2
0
2
Order By: Relevance
“…In Brazil, Scheler et al (2022) compared the deaths of pregnant and non-pregnant women during the first and second waves of the pandemic [24]. The authors demonstrated that maternal deaths from COVID-19 increased in the second wave compared with the first wave, and this increase was greater in patients with comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, Scheler et al (2022) compared the deaths of pregnant and non-pregnant women during the first and second waves of the pandemic [24]. The authors demonstrated that maternal deaths from COVID-19 increased in the second wave compared with the first wave, and this increase was greater in patients with comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…Houve um aumento expressivo da COVID-19 em 2021 em quase todos os estados brasileiros, no entanto, esse aumento foi mais acentuado no Norte do Brasil, epicentro da primeira onda de infecções. 25 Um estudo retrospectivo aponta que gestantes tiveram uma maior frequência de admissão na UTI, mortalidade, pré-eclâmpsia/eclâmpsia, hipertensão gestacional, hemorragia pós-parto, sofrimento fetal e cesariana de emergência. 29 Um estudo multicêntrico revelou um total de mulheres com hipertensão grave (94%) (6.315/6.706), enquanto 349 casos apresentaram disfunção ou falência orgânica.…”
Section: Fatores De Risco Vulnerabilidade E Características Da Covid-...unclassified
“…In the obstetric group, the rate increased from 7.7% to 15.4%, while in the non-obstetric group, it increased from 13.9% to 22.9% from 2020 to 2021. Among women with comorbidities, the mortality rate increased by 1.7 times (from 13.3% to 23.3%) and by 1.4 times (from 22.8% to 31.4%) [ 18 ]. A retrospective time series study using the Holt-Winters exponential smoothing additive model revealed devastating consequences for maternal mortality during the COVID-19 pandemic in the state of Bahia, Brazil [ 19 ].…”
Section: Introductionmentioning
confidence: 99%